Identification of Stable and Multiple Environment Interaction QTLs and Candidate Genes for Fiber Productive Traits Under Irrigated and Water Stress Conditions Using Intraspecific RILs of Gossypium hirsutum var. MCU5 X TCH1218 - Boopathi, Narayanan Manikanda; Tiwari, Gopal Ji; Jena, Satya Narayan; Nandhini, Kemparaj; Sri Subalakhshmi, V. K. I.; Shyamala, Pilla; Joshi, Babita; Premalatha, Nallathambi; Rajeswari, S. (Frontiers in Plant Science, 2022)
Cotton productivity under water stressed conditions are controlled by multiple quantitative trait loci (QTL) and enhancement of these productivity traits under stress is crucial for genetic improvement of upland cotton, G. hirsutum. The present study has constructed a genetic map covering a total span length of 4,416 cM with an average distance of 8.76 cM between markers using an intra-specific recombinant inbred lines (RILs) derived from a cross between G. hirsutum var. MCU5 and TCH1218. Though 2,457 polymorphic SNPs were detected between parents using the CottonSNP50K assay, only 504 SNPs were found to be useful for construction of genetic map as several SNPs have shown >20% missing data, segregation distortion and duplication. However, those genetically mapped SNPs of this study have shown collinearity with the physical map of the reference genome sequence (G. hirsutum var.TM1), which suggested that there was no chromosomal rearrangement among the investigated mapping population. Phenotypic data were collected from RILs that were evaluated under multi-environments and seasons and QTL analysis both under irrigated and water stress conditions have detected a total of 53 QTLs controlling plant height, number of sympodial branches, boll number and boll weight. It was also found that nine hot spot QTLs that were not only colocalized for more than one investigated trait but also stable (identified at least in two seasons / locations) and major (having > 10 % of phenotypic variation for at least one trait that colocalized in that region) and putative candidate genes specific to abiotic stress resistance in between the flanking markers of these QTLs have also been identified. Besides, few of them have previously reported across the genetic backgrounds. Thus, major and stable QTLs identified in the present study would contribute to improve cotton productivity under water limited environments through marker-assisted selection.